Persepsi Wisatawan Domestik Terhadap Efektivitas Strategi Promosi di Museum Benteng Vredeburg Yogyakarta - , SILMIA NOR FATIKHA; , Fahmi Prihantoro, S.S, S.H, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cultural tourism is one of the most popular tourist by domestic tourist If you visit Yogyakarta City. Vredeburg Museum is a museum of heritage-based cultural tourism. Historical Building Museum Vredeburg Yogyakarta is one of the tourist attraction that is attract potential tourists to visit. From the Promotion conducted by the museum needs to know the level of effectiveness through tourist Perceptions. This research discusses about domestic tourists perception of the effectiveness of promotional strategy conducted by the Museum Vredeburg Yogyakarta. The method used in this research is the combination between the method incorporation of quantitative and qualitative research methods in sequence. The purpose of this research was to determine how perceptions of the effectiveness of domestic tourist promotional strategy that has been done by the Museum Vredeburg Yogyakarta. The results of this research indicate that the level of effectiveness perceived by domestic tourists on the effectiveness of promotional strategies that have been conducted by the Museum of Yogyakarta Vredeburg was effective. This is caused by a lack of range spread of the campaign carried out by the museum. That strategy told that have been effectiveness because can improve tourist visit every year.